2023
DOI: 10.3389/fcimb.2023.1092118
|View full text |Cite
|
Sign up to set email alerts
|

Gut-joint axis: Gut dysbiosis can contribute to the onset of rheumatoid arthritis via multiple pathways

Abstract: Rheumatoid Arthritis (RA) is an autoimmune disease characterized by loss of immune tolerance and chronic inflammation. It is pathogenesis complex and includes interaction between genetic and environmental factors. Current evidence supports the hypothesis that gut dysbiosis may play the role of environmental triggers of arthritis in animals and humans. Progress in the understanding of the gut microbiome and RA. has been remarkable in the last decade. In vitro and in vivo experiments revealed that gut dysbiosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 131 publications
0
17
0
1
Order By: Relevance
“…The imbalance of GM may be involved in the pathogenesis of RA, but the mechanism of the gut-joint axis remains incompletely understood, which may be through the activation and differentiation of innate and acquired immune cells and sustained immune inflammatory response. [28] Given the different disease severity and outcome between seronegative and seropositive RA, we applied a two-sample MR approach to comprehensively explore the causal relationship between GM and RA subgroups (seropositive RA and seronegative RA). Our study found that Alloprevotella and Christensenellaceae R 7 group were negatively related to the risk of seropositive, and Ruminococcaceae UCG002 was positively associated with the seropositive RA risk.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance of GM may be involved in the pathogenesis of RA, but the mechanism of the gut-joint axis remains incompletely understood, which may be through the activation and differentiation of innate and acquired immune cells and sustained immune inflammatory response. [28] Given the different disease severity and outcome between seronegative and seropositive RA, we applied a two-sample MR approach to comprehensively explore the causal relationship between GM and RA subgroups (seropositive RA and seronegative RA). Our study found that Alloprevotella and Christensenellaceae R 7 group were negatively related to the risk of seropositive, and Ruminococcaceae UCG002 was positively associated with the seropositive RA risk.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between gut microbiota and joint diseases is often described in terms of the “gut–joint axis” ( Zaiss et al, 2021 ). As part of the gut–joint axis, dysbiosis of gut microbiota can cause immune system disorders and a sustained immune inflammatory response, leading to the occurrence and development of synovitis and tenosynovitis ( Romero-Figueroa et al, 2023 ). To date, there has been accumulating evidence that the gut microbiota is involved in human joint diseases through multiple pathways ( Yang and Cong, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to modifying immune functions, gut dysbiosis is hypothesised to contribute to RA pathology by disrupting the gut barrier function, which would facilitate the translocation of bacteria or their components/products into the lamina propria, spreading systemically and eventually leading to inflammatory responses [ 142 ]. Impaired barrier function has been reported in individuals with pre-clinical RA, early onset RA and fully established RA [ 112 , 143 ].…”
Section: Leaky Gut and Diseasesmentioning
confidence: 99%